Assessment of the symptoms of bruxism in young people in the last high-school grades - Maciejewska-Szaniec, Zofia; Maciejewska, Barbara; Mehr, Katarzyna; Piotrowski, Paweł (Family Medicine & Primary Care Review, 2016)
Background . Parafunctions are involuntary habits harmful to the chewing system. Tooth contact parafunctions are developed mostly under high emotional tension associated with stress. One of them is bruxism, i.e. teeth clenching and/or grinding. Young people in the last high-school grades are a group particularly predisposed to developing parafunctions due to high mental tension and long-lasting stress associated with the matura examination. Objectives . Assessment of the symptoms of bruxism in young people in the last high-school grades 30 days before the matura examination. Material and methods. 109 students (58 girls, 51 boys; aged 18.07 ± 0.26 years) examined 30 days before the matura examination. Every subject had a medical interview in the form of a survey containing questions about parafunctions and symptoms of dysfunction of the stomatognathic system, a medical interview, and a dental examination, including the symptoms of bruxism (vertical cracks within the enamel of the incisors and canines, teeth impressions on the side of the tongue body, palpation tenderness of the muscles of the chewing system). Results . The incidence of bruxism symptoms in the investigated group was 76.1% (83 students). Only 38.5% (42) students were aware of the problem of bruxism and reported it in at least one survey response. Higher incidence of the parafunction was observed in girls (teeth clenching under stress p = 0.0001; morning pain of the facial muscles p = 0.0393). The most common symptoms of bruxism were: increased tenderness of the muscles of mastication (71.5%) and teeth abrasion (50.5%). Conclusions . 1. The symptoms of bruxism are present in most of the investigated young people, along with a poor awareness of the presence of this parafunction 2. The most common symptom of bruxism was palpation tenderness of the muscles of mastication.